Structural Racism, Managerialism, and the Future of the Human Services: Rewriting the Rules. Issue 1 (22nd November 2021) - Abramovitz, Mimi; Zelnick, Jennifer R
Abstract: Over the past several decades, the introduction of the business model, managerialism, into the human services has led to dramatic changes in conditions of work and service delivery. This metric-driven approach increased the emphasis on measured performance outcomes and undercut the mission-driven nature of human services organizations. In 2020, the COVID-19 pandemic and widespread protests against racial injustice exposed routinely ignored structural racism long embedded in our social institutions. This reckoning led social workers to re-examine professional practices, organizational structures, and public policies through a critical, antiracist lens. Applying a racial justice lens to their study of the impact of managerialism in the human services workplace, authors identified troubling evidence of systemic racism in leadership hierarchies, worker control/surveillance on the job, quality of the physical work environment, exposure to workplace violence, exclusion by microinequities, and agency commitment to social justice. Worker resistance, ethical dilemmas, and well-being also varied by race. To become an antiracist profession, social work must seek long-term change in the human services workplace. The following analysis of the combined negative impact of managerialism and structural racism on human services organizations names the problem and presses us to rewrite the rules so we become a racial justice profession.